Prebiotics modulate the microbiota–gut–brain axis and ameliorate cognitive impairment in APP/PS1 mice. - Zhang, Shujuan; Lv, Shuang; Li, Yiming; Wei, Dongfeng; Zhou, Xiao; Niu, Xiaoqian; Yang, Ziyuan; Song, Weiqun; Zhang, Zhanjun; Peng, Dantao (European Journal of Nutrition, 2023)
Purpose: Prebiotics, including fructo-oligosaccharides (FOS) and galacto-oligosaccharides (GOS), stimulate beneficial gut bacteria and may be helpful for patients with Alzheimer's disease (AD). This study aimed to compare the effects of FOS and GOS, alone or in combination, on AD mice and to identify their underlying mechanisms. Methods: Six-month-old APP/PS1 mice and wild-type mice were orally administered FOS, GOS, FOS + GOS or water by gavage for 6 weeks and then subjected to relative assays, including behavioral tests, biochemical assays and 16S rRNA sequencing. Results: Through behavioral tests, we found that GOS had the best effect on reversing cognitive impairment in APP/PS1 mice, followed by FOS + GOS, while FOS had no effect. Through biochemical techniques, we found that GOS and FOS + GOS had effects on multiple targets, including diminishing Aβ burden and proinflammatory IL-1β and IL-6 levels, and changing the concentrations of neurotransmitters GABA and 5-HT in the brain. In contrast, FOS had only a slight anti-inflammatory effect. Moreover, through 16S rRNA sequencing, we found that prebiotics changed composition of gut microbiota. Notably, GOS increased relative abundance of Lactobacillus, FOS increased that of Bifidobacterium, and FOS + GOS increased that of both. Furthermore, prebiotics downregulated the expression levels of proteins of the TLR4-Myd88-NF-κB pathway in the colons and cortexes, suggesting the involvement of gut–brain mechanism in alleviating neuroinflammation. Conclusion: Among the three prebiotics, GOS was the optimal one to alleviate cognitive impairment in APP/PS1 mice and the mechanism was attributed to its multi-target role in alleviating Aβ pathology and neuroinflammation, changing neurotransmitter concentrations, and modulating gut microbiota.